"Indians, bureaucrats and Land : The Dawes Act and the decline of Indian farming" - "Carlson, Leonard A." (London, 1981)
This book covers the following topics Federal Indian policy and Dawes Act; Implementing the Act: A policy in practice; Allotment's Impact on Indian Farming etc.
Keywords: Indians of North America-Land tenure